CRITICAL FACTORS OF INFORMATION TECHNOLOGY INFRASTRUCTURE QUALITY FOR ENHANCING ENVIRONMENTAL COMPETENCIES OF THE INDONESIAN ORGANIZATIONS - Antoni, Darius (JURNAL ILMIAH MATRIK, 2015)
Information Technology (IT) can be adopted as a capability of organizations to improve its environmental performance. The purpose of this research is to develop IT infrastructure quality model and its environmental competencies of IT in order to improve its environmental performance. The model is developed based on the resource-based view as theoretical foundation and related literature including green IT. The validity of the model is tested using structural equation modelling based on data collected from the Indonesian ICT industry. Findings show that the IT infrastructure quality is critical abilities of an organisation used for developing environmental competencies of IT. It also indicates that the environmental competencies of organisations are positively associated with IT infrastructure quality. A new model of IT infrastructure quality constitutes an original contribution to the information system literature especially in an area the relationship between IT infrastructure quality and environmental performance.